The investigation of cyclin-di gene expression using sybr green 1 based real-time pcr in bladder cancer - Aisya, Zulkifli (Universiti Sains Malaysia, 2009)
Bladder cancer is one of the most common malignancies in developed countries while transitional cell carcinomas (TCC) are the origin of more than 90% of diagnosed bladder cancers. Patients diagnosed with bladder cancer basically belong to two clinically distinct groups, namely non-muscle invasive (which are papillary pattern) and muscle invasive (which are solid). These carcinomas pose the greatest clinical problems due to the high recurrence of non-muscle invasive tumors even after transurethral resection of the tumors. At present, there are no clinically useful markers available for identifying bladder cancer patients with a high risk of disease recurrence or progression. Initial aim of this study was to investigate by using gene expression level of Cyclin-01. The experiment was carried out by using SBYR Green 1 based Real-Time PCR analysis. However, the result was not achieved as expected. This is due to some undetermined and invalid result few factors such as contamination, mispairing of the primer and primer dimer. Therefore the investigation of the factor that contributes to invalidation was investigated by using previous journals.